R&D information and market valuation: empirical evidence from Malaysian listed firms / Sunarti Halid ... [et al.] - Halid, Sunarti; Adam, Amizahanum; Ibrahim, Marina; Ahmad Tarmizi, Masetah; Ibrahim, Muhd Kamil (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2017)
Research and Development (hereafter R&D) is an expensive activity where it requires an investment of a certain amount of capital with the belief that they would result in some increased benefits in the future periods. Traditionally, firms have supported R&D because the technological improvements made possible by innovation allow them to better productivity, succeeded in markets and meet the regulatory demands. In relation to this, the major aim of this study is to understand and acknowledge the value relevance of R&D in market valuation. The study only focuses on listed companies in Malaysia for the year 2000 until 2012. This study empirically investigated the association between R&D information in determining and explaining the market value. The study also to identify a relationship between R&D with all other assets. Furthermore, we examined the relationship between the R&D and the sign of earnings items. An equity valuation model based on the modified balance sheet identity was used to permit R&D and other assets to have separate empirical coefficient values. This study found weak empirical support at best for the value relevance of R&D at the firm level. However, the market was taken into consideration the Book Value of Net Asset (BVNA) in determining the firm’s equity value as compared to R&D. The results also indicated that the market’s valuation of R&D are expected to be priced differently from other assets during the period of study. In addition, our results, provided evidence that there is no significant relationship between R&D information and the sign of earnings items.